THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO IMPROVES WRITING SKILLS - Destri Yulandari, Naurah; Mukrim, Mukrim; Rita, Ferry; Budi, Budi (Tadulako University, 2023)
The objective of this research is to find out whether the use of the Cooperative Integrated Reading and Composition (CIRC) method of the eleventh-grade students of SMA Negeri 7 Palu can improve the students' writing skills or not; the researchers applied a quasi-experimental design which involved experimental class and control class. The population of this research was the eleventh-grade students at SMA Negeri 7 Palu. The researchers selected the sample by using a purposive sampling technique. The sample of this research was the students of XI 3(experimental class) and XI 1 (control class), which were both classes consisting of 32 students. The technique of data collection was tested (pre-test and post-test). The experimental class was treated by applying the CIRC method, while the method did not use by the control class. The result of the data analysis showed that there was a significant difference between the pre-test and post-test. The researchers found a significant difference between the results of the experimental class. It was proved by applying the testing hypothesis. The researchers found that the t-counted (3.29) was higher than the t-table (2.001). It means that the hypothesis was accepted. In conclusion, using the CIRC method effectively improves the writing skills of the eleventh-grade students of SMA Negeri 7 Palu.